La production de viande en Adamaoua Camerounais - Dumas, R.; Lhoste, Philippe (1971)
Meat production in the Adamawa was investigated. Comparative data on cattle meat production, seasonal variation of production of indigenous cattle breeds and Fulani x Brahman cattle crossbreeds, with reference to weight gain and carcass yield included.